Effectiveness of Facilitated Tucking on Physiological and Behavioral Responses among Neonates Receiving Hepatitis B Vaccination (International Journal of Nursing Education, 2020)
The study was conducted to evaluate the effectiveness of Facilitated tucking on Physiological and Behavioralresponses among neonates receiving Hepatitis B vaccination. Quasi experimental non-randomized controlgroup design was adopted for the study. The structured questionnaire was developed to collect the data.The sample were selected by purposive sampling technique and data collection was carried out among60 neonates in a selected hospital. Pretest and posttest conducted before and after facilitated tucking.The finding reveals that the physiological responses of ‘t’ value in heart rate was 3.01 respiration 1.52and oxygen saturation 3.59 and behavioural responses of ‘t’ value was 5.6 which significant at p<0.05. Itshows that Facilitated tucking was effective in enhancing physiological and behavioral responses amongneonates. There was a significant association between the age, gender, weight of neonates with physiologicaland behavioural responses. The study concluded that providing facilitated tucking was very effective inenhancing physiological and behavioral responses among neonates.